Paediatric goal management training in patients with acquired brain injury: study protocol for a randomised controlled trial - Eva Skovlund; Ruth Elizabeth Hypher; Anne Elisabeth Brandt; Kari Risnes; Torstein Baade Rø; Stein Andersson; Torun Gangaune Finnanger; Jan Stubberud (BMJ Open)
Introduction Compromised integrity of the brain due to paediatric acquired brain injury (pABI) has been associated with cognitive impairment, particularly executive dysfunction, in addition to somatic and emotional symptoms and reduced everyday function. Goal Management Training (GMT) is a cognitive rehabilitation intervention for improving executive function (EF) that has received empirical support in studies of adults with ABI. The purpose of the present study is to determine the efficacy of a recently developed paediatric version of GMT (pGMT) for children and adolescents with ABI and reported executive dysfunction.Methods and analysis This study protocol describes a parallel randomised controlled trial including allocation concealment and assessor blinding. Eighty survivors after pABI, aged 10–17 years at the time of intervention, will be recruited. Participants will be randomly allocated to either pGMT (n=40) or a psychoeducative control intervention (n=40; paediatric Brain Health Workshop). Both interventions consist of seven group sessions for participants and parents, followed by external cueing and telephone counselling. The study also includes involvement of teachers. Assessments will be performed at baseline, immediately postintervention and at 6 months’ follow-up. Primary outcome measure will be changes in daily life EF as reported by parents (The Behavior Rating Inventory of Executive Function). Secondary outcomes include other assessments of EF (neuropsychological tests and questionnaires). Furthermore, we aim to assess generalisation effects of pGMT on other cognitive functions, as well as emotional, behavioural, adaptive and family function, academic performance, fatigue and quality of life.Ethics and dissemination Results from this study will be disseminated to relevant research, clinical, health service and patient communities through publications in peer-reviewed and popular science journals, in addition to presentations at scientific conferences. The study will be conducted in accordance with the Helsinki declaration and the Ethical Research Involving Children (ChildWatch International and Unicef). In accordance to Good Clinical Practice our study includes safety and quality monitoring guarantees in compliance with research ethics and safety. The trial will be reported in accordance with the Consolidated Standards of Reporting Trials 2010 statement and Standard Protocol Items for Reporting in Trials recommendations, in addition to being registered at ClinicalTrials.gov. The study has been approved by the Regional Committees for Medical and Health Research Ethics Norway (2017/772).Trial registration number NCT03215342.